Neolithic mortuary practice in Orkney (Proceedings of the Society of Antiquaries of Scotland, 2007)
The human skeletal remains from the Neolithic chambered cairn of Isbister, Orkney were re-examined to test the accuracy of observations reported in the published analysis. During the examination, pathological lesions, signs of weathering and other taphonomic markers were recorded. Two marked disparities between the study and the published report were discovered: the Isbister population was found to display a high prevalence rate of pathological symptoms not previously described; and the bones were found not to display any great degree of the weathering, bleaching and other erosion remarked upon in the published literature. Doubt is also cast on the published calculation of minimum number of individuals interred. It is argued that the most likely explanation for the apparent differences in results is the systematic misinterpretation of pathological symptoms as evidence of taphonomic processes. It is suggested that there is no supporting evidence for the view that external exposure or preliminary disarticulation occurred prior to interment in Isbister chambered cairn.